PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KOMUNIKASI INTERPERSONAL TERHADAP MOTIVASI BERPRESTASI GURU SMA DI RAYON 11 KOTA JAKARTA SELATAN - Ujang Syaifudin Sumaji (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research was conducted in the Districts of Tebet and Setiabudi, with the method of field research through surveys, using questionnaires. The target population is high school teachers, using proportional random sampling technique, the total population is 156 and the total sample is 112 people. Test the instrument to get the validity of the statement items and the reliability of the instrument with Pearson Product Moment and Alpha Cronbach. The principal's transformational leadership instrument has a reliability of rtt = 0.94 interpersonal communication has a reliability of rtt = 0.94, and teacher achievement motivation has a reliability of rtt = 0.96. The influence forecast was analyzed using a single simple regression. The results are concluded that: 1) there is a direct positive effect of the principal's transformational leadership (X1) on teacher achievement motivation (X3) obtaining a regression equation, = 52.497 + 0.654X1 correlation coefficient r31 =) obtaining a regression equation of 0.597 and path coefficient P31 = 3.317 at the significance level = 0.05, (2) there is a direct positive influence of interpersonal communication (X2) on teacher achievement motivation (X3 obtains the equation correlation coefficient r32 = 0.671 and path coefficient P32 = 5.592 at the significance level = 0.05 (3) there is a positive influence on the principal's transformational leadership (X1) on interpersonal communication (X2) obtaining the regression equation and the correlation coefficient r12 = 0.631 and the coefficient of determination P21 = 8.524 at the significance level = 0.05.